Effects of the Invasion of Caulerpa cylindracea in a Cymodocea nodosa Meadow in the Northern Adriatic Sea - Najdek, Mirjana; Korlević, Marino; Paliaga, Paolo; Markovski, Marsej; Ivančić, Ingrid; Iveša, Ljiljana; Felja, Igor; Herndl, Gerhard J. (Frontiers in Marine Science, 2020)
The effect of the presence of invasive macroalgae Caulerpa cylindracea Sonder in the seagrass meadow Cymodocea nodosa (Ucria) Ascherson was studied by comparing the dynamics of biological and physicochemical parameters in the tissues of these two macrophytes and in the sediments underlying an invaded meadow (mixed settlement) and a C. cylindracea monospecific settlement. The study was conducted for 15 months, encompassing two summers during 2017 and 2018 (July – September) when maximum C. nodosa growth occurs. During 2017 C. cylindracea biomasses in the mixed settlement (79.5 ± 28.2 – 264.6 ± 65.1 gm-2) were lower than in its monospecific stands (113.4 ± 48.0 – 399.3 ± 56.3 gm-2). In the same period, less reducing conditions in the sediment underlying the mixed settlement were indicated by deeper redox transition depths (RTD: 8–12 mm) than those observed below the C. cylindracea monospecific settlement (RTD: 4–7 mm). In June 2018, C. cylindracea proliferated in both settlements reaching very similar biomasses that were maintained until September 2018 (mixed: 131.5 ± 23.0 – 172.5 ± 16.3 gm-2; monospecific: 162.8 ± 32.5 – 178.8 ± 30.0 gm-2). In parallel, a considerable lowering of RTD (5–7 mm) under the mixed settlement indicated the progression of stronger reducing conditions similar to those observed under the monospecific settlement (RTD: 0–7 mm). This alteration was followed by a decrease in C. nodosa below-ground biomass (89.3 ± 16.0 – 140.3 ± 24.3 gm-2), that became considerably lower than in the same period of 2017 (242.3 ± 44.3 – 346.9 ± 32.1 gm-2). At the same time, the above-ground biomass of C. nodosa (72.3 ± 14.8 – 110.3 ± 13.4 gm-2) showed no difference to the summer of 2017 (69.0 ± 15.4 – 116.0 ± 37.4 gm-2). The resulting increase of the above- to below-ground biomass ratio indicated the disruption of the meadow stability. More intense spawning of C. cylindracea in the mixed settlement during the summer 2018, hindered its expected proliferation in October 2018, while the below-ground biomass of C. nodosa increased concomitantly with the deepening of the RTD suggesting a possible recovery of the meadow stability.